Pengaruh Implementasi Core Value Aparatur Sipil Negara terhadap Kualitas Pelayanan Publik di Kecamatan Padalarang - Rahmat Kurniawan; Lukman Munawar Fauzi; Dahly Sukmapryandhika (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study aims to examine the effect of ASN Core Value implementation on the quality of public services in Padalarang District, West Bandung Regency. Through a quantitative descriptive approach and linear regression analysis, this study evaluates the relationship between the implementation of ASN Core Values, known by the acronym BerAKHLAK (Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative), with the quality of public services. The results of the study indicate that there is a significant and positive relationship between the implementation of ASN Core Values ​​and improving the quality of public services. The regression coefficient of 0.457 and the correlation value of 0.613 indicate that the implementation of BerAKHLAK values ​​can significantly improve the quality of public services.